Enjoying a Quiet Life Even During a Great Recession? Evidence From the Greek Olive Oil Industry - KERAMIDOU, Ioanna; MIMIS, Angelos (Theoretical and Practical Research in Economic Fields; Vol 14 No 1 (2023): TPREF, Volume XIV, Issue 1(27), Summer 2023, 2023)
The research investigates the link between market concentration and efficiency by analyzing the Greek olive oil industry data from 2006 to 2014. Unlike previous research on this issue, which focused on the impact of overall company efficiency on market power, we study the association between the three types of firm efficiency (profit, technical, and scale) and market concentration. Our theoretical framework and research assumptions were not predefined but were generated by modelling the data from the Greek oil olive sector through data mining techniques. The predicted causal relationships constructed in the preceding stage were investigated using partial least squares path modeling (PLS-PM) regression. The results show a significant negative relationship between market concentration and technical and profit efficiency. The paucity of completion resulted in prolonged firm inefficiencies, demonstrating that Greek enterprises, even during a severe recession, refrained from rigorous efforts to enhance technical and profit efficiency as they would in a competitive market, preferring instead to live a quiet life (QL). This study has several policy implications for regulators and policymakers, such as extending antitrust rules, which may enhance company efficiency and competitiveness.